Alkali-activated pavement concrete prepared from mountain tunnel slag and preparation method of alkali-activated pavement concrete

By using alkali excitation technology and recycling aggregates in tunnel pavement concrete, the problems of low early strength of tunnel pavement and unused tunnel slag are solved, and the green economic benefits of efficient construction and environmental protection are achieved.

CN119461983APending Publication Date: 2025-02-18GUANGZHOU MUNICIPAL ENG MASCH CO +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411689961.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The early strength of the existing tunnel pavement concrete is low, which hinders the progress of tunnel concrete pavement construction. At the same time, the tunnel slag has not been recycled, resulting in an increase in land resource consumption and cement production is accompanied by a large amount of CO2 emissions.

Method used

The alkali excitation technology is used to replace cement with NaOH solution, stimulate the gelling characteristics of fly ash and slag powder, improve the early strength of concrete, and form a recycled coarse and fine aggregate by crushing and shaping the tunnel slag.

Benefits of technology

It significantly improves the early compressive strength of concrete, shortens construction time, improves the bearing capacity of pavement structure, and realizes the recycling of tunnel slag, reducing land resource consumption and CO2 emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461983A_ABST
    Figure CN119461983A_ABST
Patent Text Reader

Abstract

The invention relates to alkali-activated pavement concrete prepared from mountain tunnel slag and a preparation method of the alkali-activated pavement concrete. The alkali-activated pavement concrete is prepared from the following raw materials in parts by mass: 101.6 to 114.4 parts of water, 25.6 to 38.4 parts of NaOH solid, 80 to 160 parts of fly ash, 40 to 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate superplasticizer. The alkali-activated pavement concrete has the characteristics of high early strength, greenness, low carbon and recyclability, turns waste into wealth through cyclic utilization of the fly ash, the slag powder and the tunnel hole slag, and belongs to the field of rigid concrete materials for paving tunnel pavements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rigid paving concrete materials for tunnel pavements, and in particular to an alkali-activated pavement concrete using mountain tunnel slag and a preparation method thereof. Background Art

[0002] With the development of the economy and society, people pay more and more attention to protecting the environment. In recent years, the scale of tunnel projects has continued to expand. Among them, the recycling of tunnel slag is an important means to achieve the goals of green, low-carbon and land resource conservation.

[0003] At present, tunnel pavement concrete mainly uses cement as a cementitious material, and commercial coarse and fine aggregates are purchased as concrete raw materials. The production of cement is often accompanied by a large amount of CO2 greenhouse gas emissions. At the same time, tunnel slag has not been recycled through corresponding technical means, resulting in a large amount of tunnel slag being abandoned, increasing the consumption of land resources. The existing tunnel pavement concrete has a low early strength, which hinders the progress of tunnel concrete pavement construction. Summary of the invention

[0004] In view of the technical problems existing in the prior art, the purpose of the present invention is to provide an alkali-activated pavement concrete using mountain tunnel slag and a preparation method thereof, wherein NaOH solution can be used to completely replace cement, thereby reducing the CO2 emission during cement production, stimulating its gelling properties through alkaline substances, improving the early strength of concrete, and facilitating the construction of tunnel pavement and improving the bearing capacity of the pavement structure. At the same time, tunnel slag is used as coarse and fine aggregate through rolling processing, thereby reducing the land resource occupation of abandoned slag, allowing the tunnel slag to be recycled, and by using industrial waste such as fly ash and slag powder, "turning waste into treasure" is achieved, which is in line with the current environmental protection concept of green and low carbon and reducing energy consumption, and has significant green economic benefits.

[0005] In order to achieve the above object, the present invention adopts the following technical solution: An alkali-activated pavement concrete using mountain tunnel slag comprises the following raw materials in parts by weight: 101.6-114.4 parts of water, 25.6-38.4 parts of NaOH solid, 80-160 parts of fly ash, 40-120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylic acid water reducer.

[0006] As a preferred embodiment, the alkali-activated pavement concrete at a concentration of 8 mol / L NaOH solution includes the following raw materials in parts by weight: 114.4 parts of water, 25.6 parts of NaOH solid, 80 parts of fly ash, 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; Among them, 114.4 parts of water include 60 parts of mixing water and 54.4 parts of dissolved water; The fly ash was grade II with a particle size of 83 mm, and the slag powder was grade S95 with a particle size of 16 mm; 450 parts of fine aggregate include: 9 parts of machine-made sand with a particle size of 0-0.15mm, 35 parts of machine-made sand with a particle size of 0.15-0.3mm, 158 parts of machine-made sand with a particle size of 0.3-0.6mm, 158 parts of machine-made sand with a particle size of 0.6-1.18mm, 45 parts of machine-made sand with a particle size of 1.18-2.36mm and 45 parts of machine-made sand with a particle size of 2.36-4.75mm; The coarse aggregate includes: 2 parts of impact crusher graded gravel with particle size of 0~2.36mm, 74 parts of impact crusher graded gravel with particle size of 2.36~4.75mm, 116 parts of impact crusher graded gravel with particle size of 4.75~9.5mm and 8 parts of impact crusher graded gravel with particle size of 9.5~19mm.

[0007] As a preferred embodiment, both coarse aggregate and fine aggregate are obtained by crushing and shaping tunnel slag, the apparent density of coarse aggregate is 2.618t / m³, the bulk density is 1.580t / m³, the water absorption is 2.4%, and the crushing value is 14.4%; the apparent density of fine aggregate is 2.7t / m³, the bulk density is 1.511t / m³, the mud content does not exceed 0.2%, the water content is 1.99%, and the fineness modulus is 2.97. As a preferred embodiment, the alkali-activated pavement concrete at a concentration of 10mol / LNaOH solution includes the following raw materials in parts by mass: 108 parts of water, 32 parts of NaOH solid, 80 parts of fly ash, 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; wherein, 108 parts of water include 60 parts of mixing water and 48 parts of dissolved water.

[0008] As a preferred embodiment, alkali-activated pavement concrete at a concentration of 12 mol / L NaOH solution includes the following raw materials in parts by mass: 101.6 parts of water, 38.4 parts of NaOH solid, 80 parts of fly ash, 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; wherein, 101.6 parts of water include 60 parts of mixing water and 41.6 parts of dissolved water.

[0009] As a preferred embodiment, when the slag replacement rate is 20%, the alkali-activated pavement concrete at a concentration of 10 mol / L NaOH solution includes the following raw materials in parts by weight: 108 parts of water, 32 parts of NaOH solid, 160 parts of fly ash, 40 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; Among them, 108 parts of water include 60 parts of mixing water and 48 parts of dissolving water; The fly ash was grade II with a particle size of 83 mm, and the slag powder was grade S95 with a particle size of 16 mm; 450 parts of fine aggregate include 9 parts of machine-made sand with a particle size of 0-0.15mm, 35 parts of machine-made sand with a particle size of 0.15-0.3mm, 158 parts of machine-made sand with a particle size of 0.3-0.6mm, 158 parts of machine-made sand with a particle size of 0.6-1.18mm, 45 parts of machine-made sand with a particle size of 1.18-2.36mm, and 45 parts of machine-made sand with a particle size of 2.36-4.75mm. The coarse aggregate includes 2 parts of impact crushed graded stone with a particle size of 0-2.36mm, 74 parts of impact crushed graded stone with a particle size of 2.36-4.75mm, 116 parts of impact crushed graded stone with a particle size of 4.75-9.5mm, and 8 parts of impact crushed graded stone with a particle size of 9.5-19mm; The apparent density of coarse aggregate is 2.62t / m³, the volume density is 1.581t / m³, the water absorption is 2.4%, and the crushing value is 14.4%; the apparent density of fine aggregate is 2.41t / m³, the bulk density is 1.514t / m³, the mud content does not exceed 0.2%, the water content is 1.99%, and the fineness modulus is 2.97.

[0010] As a preference, when the slag replacement rate is 40%, the alkali-activated pavement concrete at a concentration of 10 mol / L NaOH solution includes the following raw materials in parts by mass: 108 parts of water, 32 parts of NaOH solid, 120 parts of fly ash, 80 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylic acid water reducer; the 108 parts of water include 60 parts of mixing water and 48 parts of dissolved water.

[0011] As a preference, when the slag replacement rate is 60%, the alkali-activated pavement concrete at a concentration of 10 mol / L NaOH solution includes the following raw materials in parts by mass: 108 parts of water, 32 parts of NaOH solid, 80 parts of fly ash, 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylic acid water reducer, and the 108 parts of water include 60 parts of mixing water and 48 parts of dissolved water.

[0012] A method for preparing alkali-activated pavement concrete using mountain tunnel slag under conditions of different molar concentrations of sodium hydroxide solution comprises the following steps: S1: preparing an alkali-activated mineral admixture mixture, mixing fly ash and slag powder according to mass percentage, dry-mixing and uniformly pouring into a stirring pot, and stirring at a constant speed for 30 seconds to obtain a first mixture; S2: adding mixing water and polycarboxylate water reducer, adding the mixing water and polycarboxylate water reducer into the first mixed material according to the mass percentage, stirring at a constant speed for 1 minute until the mixture is uniform, and obtaining a second mixed material; S3: preparing a NaOH solution, mixing dissolved water and NaOH solid particles according to mass percentage, stirring at a constant speed for 1 minute until the mixture is uniformly stirred, and obtaining a third mixture; S4: pouring the prepared third mixed material into the second mixed material, stirring at a constant speed for 30 seconds until the mixture is uniform, to obtain a fourth mixed material; S5: Add the coarse aggregate and the fine aggregate into the fourth mixture according to the mass percentage, and stir at a constant speed for 2 to 3 minutes until the mixture is uniformly stirred to obtain an alkali-activated pavement concrete material; S6: Cast the test specimen, add the alkali-activated pavement concrete material into a 150×150×150mm³ mold, vibrate it with a vibrator for 1 minute until no bubbles emerge on the surface, and smooth the surface; S7: Curing, cover the mold with a film and seal it to keep it moist and maintain it, then remove the mold and place it in a standard curing room for sealing and curing for 28 days; S8: Loading test: the mechanical properties of the cured specimens are tested in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB-T50081-2019.

[0013] A method for preparing alkali-activated pavement concrete using mountain tunnel slag under different slag replacement rates comprises the following steps: S1: Prepare an alkali-activated mineral admixture mixture, mix the fly ash and slag powder according to the mass percentage, dry mix and pour into a stirring pot, stir at a constant speed for 30s to obtain a first mixture; S2: adding mixing water and polycarboxylate water reducer, adding the mixing water and polycarboxylate water reducer into the first mixture according to the mass percentage, stirring at a constant speed for 1 minute until the mixture is uniform, and obtaining the second mixture; S3: preparing a NaOH solution, mixing dissolved water and NaOH solid particles according to mass percentage, stirring at a constant speed for 1 minute until the mixture is uniformly stirred, and obtaining a third mixture; S4: pouring the prepared third mixed material into the second mixed material, stirring at a constant speed for 30 seconds until the mixture is uniform, to obtain a fourth mixed material; S5: Add the coarse aggregate and the fine aggregate into the fourth mixture according to the mass percentage, and stir at a constant speed for 2 to 3 minutes until the mixture is uniformly stirred to obtain an alkali-activated pavement concrete material; S6: Cast the test specimen, add the alkali-activated pavement concrete material into a 150×150×150mm³ mold, vibrate it with a vibrator for 1 minute until no bubbles emerge on the surface, and smooth the surface; S7: Curing, the film covers the mold and moisturizes the seal and curing, then removes the mold and places it in a standard curing room for sealing and curing for 28d; S8: Loading test: the mechanical properties of the cured specimens are tested in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB-T50081-2019.

[0014] In general, the present invention has the following advantages: 1. The alkali-activated pavement concrete using mountain tunnel slag of the present invention has a 1-day and 3-day compressive strength that can reach 46.15% and 67.89% of the 28-day compressive strength, respectively. Compared with traditional concrete, the alkali-activated pavement concrete has a faster early strength increase and higher strength, which is beneficial to speeding up the construction progress and improving the bearing capacity of the pavement structure.

[0015] 2. In the alkali-activated pavement concrete using mountain tunnel slag of the present invention, the optimal molar concentration of the sodium hydroxide solution is about 10 M. Compared with the molar concentrations of 8 M and 12 M, when the molar concentration is 10 M, the compressive strength of the concrete increases by 43.96% and 20.26%, respectively. The sodium hydroxide solution can accelerate the polymerization process, while an excessively low alkaline environment will lead to insufficient hydration reaction of the concrete, and an excessively high alkaline environment will lead to precipitation of the polymerization product.

[0016] 3. The alkali-activated pavement concrete using mountain tunnel slag of the present invention, when the sodium hydroxide concentration is fixed at 10 mol / L, has a significantly improved compressive strength with the slag replacement rate increasing from 20% to 40% and from 40% to 60%, which are increased by 55.56% and 41.14% respectively.

[0017] 4. The alkali-activated pavement concrete using mountain tunnel slag of the present invention uses fly ash and slag powder and other byproducts of coal combustion and metal ore smelting as cementing materials, and does not use cement in the mix design, so that industrial waste slag can be fully reused, reducing CO2 emissions, saving energy and protecting the environment. At the same time, the coarse and fine aggregates made by recycling tunnel slag can be used as raw materials for alkali-activated pavement concrete, reducing the land resource consumption increased by the abandonment of tunnel slag, and realizing "turning waste into treasure". BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a sample with a curing age of 3 days; Figure 2 It is a sample with a curing age of 7 days; Figure 3 It is a sample with a curing age of 14 days; Figure 4 This is a sample with a curing age of 28 days.

[0019] The microstructure was analyzed using scanning electron microscopy (SEM). Figure 1~Figure 4 The following are the observation results of the microstructure of alkali-activated pavement concrete at different curing ages. Figure 1As shown in the figure, for the specimen with a curing age of 3 days, there are some partially reacted and unreacted fly ash particles on the surface, while the CSH gel, which is considered to be an unstable microstructure, is visible on a considerable part of the surface. Scanning electron microscopy also found that a small part of C-(A)-SH gel is a stable structural product formed by the chemical reaction of fly ash, slag powder and CSH gel. A large number of discrete microcracks were observed in the CSH gel paste, resulting in poor bonding behavior. Figure 2~Figure 4 As shown in Figure 2, the alkaline activation reaction is almost complete because few fly ash particles are observed. Subsequently, the free Al(OH)4 groups in the internal system of the polymer react with the CSH gel to form a stable C-(A)-SH gel microstructure in the late hydration stage. The final product exhibits a dense structure, which explains why the compressive strength of alkali-activated pavement concrete increases with the increase of curing age. Figure 1 As shown in the figure, the 3d specimens have visible micro cracks and fly ash particles on the concrete compared to the 7d, 14d, and 28d specimens. This means that the polymerization reaction is still going on and the fly ash is in the form of spherical particles. With the increase in curing days, the fly ash decreases and more C-(A)-SH gel is produced, forming a dense microstructure. For the curing age of 14 and 28 days, the hydration process is more mature and the samples have no voids. The main cracks along the interface transition zone after 7 days of curing are more obvious than those after 14 and 28 days of curing. The specimens after 28 days of curing have almost no unreacted fly ash and cracks are mainly observed in the polymer paste rather than along the interface transition zone. The polymer has good bonding properties between the paste and alkali-activated pavement concrete. DETAILED DESCRIPTION

[0020] The present invention will be further described in detail below in conjunction with specific implementation methods.

[0021] The present embodiment provides an alkali-activated pavement concrete using mountain tunnel slag, which is composed of the following raw materials in parts by mass: 101.6~114.4 parts of water (including 60 parts of mixing water and 41.6~54.4 parts of dissolved water); 25.6-38.4 parts of NaOH solid; 80-160 parts of Class II fly ash; 40~120 parts of S95 grade slag powder; 200 parts of coarse aggregate; 2 parts of impact crusher graded gravel with a particle size of 0~2.36mm; 74 parts of impact crusher graded crushed stone with a particle size of 2.36~4.75mm; 116 parts of impact crusher graded crushed stone with a particle size of 4.75-9.5 mm; 8 parts of impact crusher graded gravel with particle size of 9.5~19mm.

[0022] 450 parts of fine aggregate; 9 parts of machine-made sand with a particle size of 0-0.15 mm; 35 parts of machine-made sand with a particle size of 0.15~0.3mm; 158 parts of machine-made sand with a particle size of 0.3-0.6 mm; 158 parts of machine-made sand with a particle size of 0.6-1.18 mm; 45 parts of machine-made sand with a particle size of 1.18-2.36 mm; 45 parts of machine-made sand with particle size of 2.36~4.75mm.

[0023] 10 parts of polycarboxylate water reducer.

[0024] In some embodiments, the machine-made sand has 6 different particle sizes, and the impact crusher graded crushed stone has 4 different particle sizes. In the embodiments, on the one hand, the coarse aggregate plays a role in supporting the skeleton, and on the other hand, the fine aggregate optimizes the particle grading. At the same time, the coarse and fine aggregates made by crushing and shaping the tunnel slag are used to reduce the land resource occupation of the abandoned slag, and realize the recycling of the tunnel slag.

[0025] In some embodiments, the admixture is fly ash or slag powder. Such admixture can greatly reduce the amount of cement used, thereby reducing CO2 emissions and saving energy.

[0026] In some embodiments, the water reducer is a polycarboxylate water reducer with a water reduction rate greater than 25%. In this embodiment, the cementitious material particles are evenly dispersed, workability is improved, fluidity is increased, and water consumption is reduced, thereby improving the mechanical properties and durability of the tunnel surface alkali-activated pavement concrete material.

[0027] Example 1, an alkali-activated pavement concrete using mountain tunnel slag includes the following raw materials in parts by weight: 114.4 parts of water (including 60 parts of mixing water and 54.4 parts of dissolved water); 25.6 parts of NaOH solid; 80 parts of Class II fly ash; 120 parts of S95 grade slag powder; 200 parts of coarse aggregate; 2 parts of impact crusher graded gravel with a particle size of 0~2.36mm; 74 parts of impact crusher graded crushed stone with a particle size of 2.36~4.75mm; 116 parts of impact crusher graded crushed stone with a particle size of 4.75-9.5 mm; 8 parts of impact crusher graded gravel with particle size of 9.5~19mm.

[0028] 450 parts of fine aggregate; 9 parts of machine-made sand with a particle size of 0-0.15 mm; 35 parts of machine-made sand with a particle size of 0.15~0.3mm; 158 parts of machine-made sand with a particle size of 0.3-0.6 mm; 158 parts of machine-made sand with a particle size of 0.6-1.18 mm; 45 parts of machine-made sand with a particle size of 1.18-2.36 mm; 45 parts of machine-made sand with particle size of 2.36~4.75mm.

[0029] 10 parts of polycarboxylate water reducer.

[0030] This embodiment also provides a method for preparing alkali-activated pavement concrete using mountain tunnel slag, which is prepared according to the following steps: Step 1: Prepare an alkali-activated mineral admixture mixture. Mix fly ash and slag powder according to mass percentage, dry mix evenly, pour into a mixing pot, and stir at a constant speed for 30 seconds to obtain a first mixture; Step 2: Add mixing water and polycarboxylate water reducer. Add mixing water and polycarboxylate water reducer into the first mixed material according to the mass percentage, stir at a constant speed for 1 minute until the mixture is uniform, and obtain the second mixed material; Step 3: Prepare NaOH solution. Mix dissolved water and NaOH solid particles according to mass percentage, and stir at a constant speed for 1 minute until the mixture is uniform, to obtain a third mixture; Step 4: Pour the prepared third mixture into the second mixture, and stir at a constant speed for 30 seconds until it is uniformly stirred to obtain a fourth mixture; Step 5: Add the coarse aggregate and the fine aggregate into the fourth mixture according to the mass percentage, and stir at a constant speed for 2 to 3 minutes until the mixture is uniform, so as to obtain an alkali-activated pavement concrete material; Step 6: Casting the test specimen. Add the alkali-activated tunnel pavement concrete material into a 150×150×150mm³ mold, vibrate it with a vibrator for 1 minute until no bubbles appear on the surface, and smooth the surface; Step 7: Curing. Cover with film and seal to keep moist, then remove the mold and place in standard curing room for 28 days; Step 8: Loading test. The cured specimens are tested for relevant mechanical properties in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB-T 50081-2019.

[0031] Example 2, comprising the following raw materials in parts by weight: 108 parts of water (including 60 parts of mixing water and 48 parts of dissolving water); 32 parts of NaOH solid; The mass fractions of other raw materials are the same as those in Example 1.

[0032] Example 3, comprising the following raw materials in parts by weight: 101.6 parts of water (including 60 parts of mixing water and 41.6 parts of dissolved water); 38.4 parts of NaOH solid; The mass fractions of other raw materials are the same as those in Example 1.

[0033] Example 4, comprising the following raw materials in parts by weight: 108 parts of water (including 60 parts of mixing water and 48 parts of dissolving water); 32 parts of NaOH solid; 160 parts of Class II fly ash; 40 parts of S95 grade slag powder; The mass fractions of other raw materials are the same as those in Example 1.

[0034] Example 5, comprising the following raw materials in parts by weight: 108 parts of water (including 60 parts of mixing water and 48 parts of dissolving water); 32 parts of NaOH solid; 120 parts of Class II fly ash; 80 parts of S95 grade slag powder; The mass fractions of other raw materials are the same as those in Example 1.

[0035] Example 6, comprising the following raw materials in parts by weight: 108 parts of water (including 60 parts of mixing water and 48 parts of dissolving water); 32 parts of NaOH solid; 80 parts of Class II fly ash; 120 parts of S95 grade slag powder; The mass fractions of other raw materials are the same as those in Example 1.

[0036] Comparative Example 1: A conventional tunnel pavement concrete comprises the following raw materials in parts by weight: Mix 120 parts of water; 370 parts of cement; 610 parts of coarse aggregate; 6 parts of impact crusher graded crushed stone with a particle size of 0~2.36mm; 18 parts of impact crusher graded crushed stone with a particle size of 2.36~4.75mm; 73 parts of impact crusher graded crushed stone with a particle size of 4.75-9.5 mm; 342 parts of impact crusher graded crushed stone with a particle size of 9.5-19 mm; 171 parts of impact crusher graded gravel with particle size of 19~31.5mm.

[0037] 390 parts of fine aggregate; 4 parts of machine-made sand with a particle size of 0-0.15 mm; 47 parts of machine-made sand with a particle size of 0.15-0.3 mm; 89 parts of machine-made sand with a particle size of 0.3-0.6 mm; 86 parts of machine-made sand with a particle size of 0.6-1.18 mm; 86 parts of machine-made sand with a particle size of 1.18-2.36 mm; 78 parts of machine-made sand with particle size of 2.36~4.75mm.

[0038] 9.25 parts of admixture.

[0039] This comparative example 1 provides a method for preparing conventional tunnel pavement concrete, which is prepared according to the following steps: Step 1: Prepare a mixture of coarse and fine aggregates. Mix the coarse aggregate and fine aggregate according to the mass percentage, dry mix evenly, pour into a mixing pot, and stir at a constant speed for 30 seconds to obtain the first mixture; Step 2: Add cementitious material to the coarse and fine aggregate mixture. Add cement to the first mixture according to the mass percentage, stir at a constant speed for 1 minute until the mixture is uniform, and obtain the second mixture; Step 3: Add mixing water and polycarboxylate water reducer. Add mixing water and polycarboxylate water reducer into the second mixture according to the mass percentage, stir at a constant speed for 2-3 minutes until the mixture is uniform, and obtain a conventional tunnel pavement concrete mixture; Step 4: Casting the test piece. Add the conventional concrete mixture into the 150×150×150mm³ mold, vibrate it with a vibrator for 1 minute until no bubbles appear on the surface, and smooth the surface; Step 5: Curing. Cover with film and seal to keep moist, then remove the mold and place in standard curing room for 28 days; Step 6: Loading test. The cured specimens are tested for relevant mechanical properties in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB-T 50081-2019.

[0040] The compressive strength test was conducted on the test pieces made of alkali-activated pavement concrete using mountain tunnel slag at different NaOH solution concentrations described in Examples 1 to 3 and the test piece of Comparative Example 1. The test process was carried out in accordance with the Standard for Test Methods for Physical and Mechanical Properties of Concrete GB-T 50081-2019. The experimental data are shown in Table 1: Table 1 Compressive stress of NaOH solution at different molar concentrations in each embodiment It can be seen from Table 1 that as the molar concentration of the sodium hydroxide solution increases from 8M to 10M, the peak stress of the sample increases by 43.96%, but when the molar concentration increases from 10M to 12M, the peak stress decreases by 20.26%. This can be explained by the fact that the alkali-activated product depends on the hydroxide ion (OH) in the sodium hydroxide. - To explain, more hydroxide ions can improve the compressive strength of the product. However, during the alkali excitation process, the formation of aluminosilicate gel causes precipitation at an early stage and leads to an overly alkaline environment. Therefore, a higher sodium hydroxide molar concentration reduces the compressive strength. With the increase of the molar concentration of the sodium hydroxide solution, the development of compressive strength first increases and then decreases. Too high a molar concentration of the sodium hydroxide solution will lead to a highly alkaline environment, which hinders the dissolution of Ca(OH)2. Due to the insufficient Ca2+ content, the main hydration product is converted from CASH to NASH. Therefore, a 10M sodium hydroxide solution is the optimal molar concentration.

[0041] The 28d compressive stress peaks of Examples 1 to 3 are increased by -5.27%, 36.37%, and 13.40% respectively compared with the peak stress of Comparative Example 1. Example 1 can be close to the peak stress of Comparative Example 1, and Examples 2 and 3 can greatly exceed the peak stress of Comparative Example 1. That is, the alkali-activated pavement concrete using mountain tunnel slag can completely replace cement on the premise of being close to or reaching the peak stress of traditional pavement concrete, thereby reducing the CO2 emissions during cement production and improving the early strength of concrete, which is beneficial to speeding up the construction progress of tunnel pavement and improving the bearing capacity of pavement structure. At the same time, tunnel slag is used as coarse and fine aggregate through rolling processing, which reduces the land resource occupation of abandoned slag and realizes the recycling of tunnel slag. By using industrial waste such as fly ash and slag powder, "turning waste into treasure" is achieved, which is in line with the current green and low-carbon environmental protection concept of reducing energy consumption, and has significant green economic benefits.

[0042] The compressive strength test was performed on the standard specimens prepared by using the alkali-activated pavement concrete of mountain tunnel slag described in Examples 4 to 6 and the specimens of Comparative Example 1 after standard curing for 28 days. The test process was carried out in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB-T 50081-2019. The experimental data are shown in Table 2: Table 2 Compressive stress-strain of various embodiments at different slag replacement rates Table 2 shows the stress-strain peak comparison of the samples with different slag replacement rates at the same age of 28 days when the concentration of sodium hydroxide solution is fixed at 10 mol / L. The results shown in Table 2 show that increasing the slag replacement rate can significantly improve the compressive strength. For the sample with a fixed concentration of 10 mol / L, when the slag replacement rate is increased from 20% to 40%, the peak stress of the sample increases by 55.56%, and when the slag replacement rate is increased from 40% to 60%, the peak stress of the sample increases by 41.14%. The explanation is that the increase in the slag powder content leads to an increase in the silicon / aluminum ratio in the mixed material. This shows that the ratio of silicon in the mixture determines the relative content of AlO4 and silicate, which leads to the formation of aluminum-silicon hydrate (CASH) gel, which helps to improve the compressive strength. Therefore, at a NaOH solution concentration of 10 mol / L, a slag replacement rate of 60% is the optimal slag replacement rate.

[0043] The 28d compressive stress peak values ​​of Examples 4 to 6 are increased by -37.62%, -1.6%, and 36.97% respectively compared with the peak stress of Comparative Example 1. The peak stress of Example 4 is quite different from that of Comparative Example 1, Example 5 is close to the peak stress of Comparative Example 1, and Example 6 greatly exceeds the peak stress of Comparative Example 1. At the same time, the 28d compressive strain peak values ​​of Examples 4 to 6 are increased by -35.10%, 4.55%, and 9.09% respectively compared with the peak strain of Comparative Example 1. The peak strain of Example 4 is quite different from that of Comparative Example 1, Example 5 is close to the peak strain of Comparative Example 1, and Example 6 exceeds the peak strain of Comparative Example 1. Under the premise of approaching or reaching the peak stress of traditional pavement concrete, the alkali-activated pavement concrete using mountain tunnel slag can completely replace cement with NaOH solution, reducing the CO2 emission during cement production, stimulating its gelling properties through alkaline substances, improving the early strength of concrete, and accelerating the construction progress of tunnel pavement and improving the bearing capacity of pavement structure. At the same time, the tunnel slag is used as coarse and fine aggregates through rolling, reducing the land resource occupation of abandoned slag, and the tunnel slag can be recycled. By using industrial waste such as fly ash and slag powder, "waste is turned into treasure", which is in line with the current green and low-carbon environmental protection concept of reducing energy consumption, and the green economic benefits are significant. The compressive strength test of the standard specimen prepared by the alkali-activated pavement concrete using mountain tunnel slag described in Example 6 and the standard specimen of comparative example 1 at each age of standard curing was carried out. The test process was carried out in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB-T 50081-2019, and the experimental data are shown in Table 3: Table 3 Compressive stress-strain of Example 6 and Comparative Example 1 at different ages As can be seen from Table 3, the compressive strength of the concrete at the curing age of 1 day and 3 days in Example 6 reached 46.15% and 67.89% of the peak compressive strength, while the compressive strength of the concrete at the curing age of 1 day and 3 days in Comparative Example 1 reached 30% and 50% of the peak compressive strength, indicating that the alkali-activated pavement concrete has a faster early strength improvement than traditional concrete and has higher strength, which is conducive to accelerating the construction progress and improving the bearing capacity of the pavement structure.

[0044] The 1d and 3d compressive stress peaks in Example 6 increased by 17.97Mpa and 23.26Mpa respectively compared with the 1d and 3d compressive stress peaks in Comparative Example 1, with growth rates of 110.72% and 85.99% respectively, which fully reflects the high early strength characteristics of alkali-activated pavement concrete. At the same time, the 1d and 3d compressive strain peaks in Example 6 increased by 0.52% and 3.05% respectively compared with the 1d and 3d peak strains in Comparative Example 1, and the 1d and 3d peak strains in Example 6 and Comparative Example 1 are relatively close. Under the premise of exceeding the peak stress of traditional pavement concrete, alkali-activated pavement concrete made from mountain tunnel slag can completely replace cement with NaOH solution, reducing CO2 emissions during cement production. By stimulating its gelling properties through alkaline substances, the early strength of concrete is improved, which is beneficial to speed up the construction progress of tunnel pavement and improve the bearing capacity of pavement structure. At the same time, tunnel slag is used as coarse and fine aggregate after rolling processing, which reduces the land resource occupation of slag abandonment. Tunnel slag can be recycled, and by using industrial waste such as fly ash and slag powder, "waste is turned into treasure", which is in line with the current green and low-carbon environmental protection concept of reducing energy consumption, and has significant green economic benefits.

[0045] in conclusion In the above embodiment, axial compression load tests were conducted on 6 groups of samples to study the effects of sodium hydroxide molar concentration, slag replacement rate and curing age on the mechanical properties of alkali-activated pavement concrete, and an optimal mix ratio of alkali-activated pavement concrete using mountain tunnel slag was found. The specific conclusions are as follows: According to Table 1, by comparing the data of Examples 1 to 3, the compressive strength of Example 2 is increased more than that of Examples 1 and 3, and is increased by 22.53Mpa and 12.43Mpa respectively compared with 8mol / L and 12mol / L NaOH solutions in alkaline environments, with improvement rates of 43.96% and 20.26% respectively. The test shows that too low alkaline environment will lead to insufficient hydration reaction of concrete, and excessive alkaline environment will lead to precipitation of polymerization products, that is, the 10mol / L concentration of NaOH solution selected in Example 2 is the optimal concentration.

[0046] According to Table 2, by comparing the data of Examples 4 to 6, when the slag replacement rate is 60%, the compressive strength of Example 6 increases more than that of Examples 4 and 5, increasing by 40.35 MPa and 21.6 MPa respectively, with an improvement rate of 119.56% and 41.14% respectively, and the compressive strain decreases by 0.75×10 -3 and 0.1×10 -3 Therefore, the slag replacement rate of 60% selected in Example 6 is the optimal slag replacement rate.

[0047] According to Table 3, the compressive strength of alkali-activated pavement concrete at 1 day and 3 days can reach 46.15% and 67.89% of the 28-day compressive strength. The early compressive strength of alkali-activated pavement concrete will increase rapidly, which is conducive to speeding up the construction progress and improving the bearing capacity of the pavement structure.

[0048] Scanning electron microscopy analysis showed that the alkali-activated products could fill the voids of porous aggregate particles and had good bonding properties between the paste and alkali-activated pavement concrete.

[0049] That is, the alkali-activated pavement concrete using mountain tunnel slag provided in the above embodiment can significantly improve the early strength of tunnel pavement materials, and NaOH solution can completely replace the use of cement materials, thereby reducing CO2 emissions. At the same time, tunnel slag is used as coarse and fine aggregates after rolling processing, which reduces the land resource occupation of slag abandonment, and tunnel slag can be recycled. By using industrial waste such as fly ash and slag powder, "waste is turned into treasure", which is in line with the current green and low-carbon environmental protection concept of reducing energy consumption, and has significant green economic benefits.

[0050] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. An alkali-activated pavement concrete using mountain tunnel slag, characterized in that: The invention comprises the following raw materials in parts by weight: 101.6-114.4 parts of water, 25.6-38.4 parts of NaOH solid, 80-160 parts of fly ash, 40-120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylic acid water reducer.

2. The alkali-activated pavement concrete using mountain tunnel slag according to claim 1, characterized in that: The alkali-activated pavement concrete at a concentration of 8 mol / L NaOH solution includes the following raw materials in parts by weight: 114.4 parts of water, 25.6 parts of NaOH solid, 80 parts of fly ash, 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; Among them, 114.4 parts of water include 60 parts of mixing water and 54.4 parts of dissolved water; The fly ash was grade II with a particle size of 83 mm, and the slag powder was grade S95 with a particle size of 16 mm; 450 parts of fine aggregate include: 9 parts of machine-made sand with a particle size of 0-0.15mm, 35 parts of machine-made sand with a particle size of 0.15-0.3mm, 158 parts of machine-made sand with a particle size of 0.3-0.6mm, 158 parts of machine-made sand with a particle size of 0.6-1.18mm, 45 parts of machine-made sand with a particle size of 1.18-2.36mm and 45 parts of machine-made sand with a particle size of 2.36-4.75mm; The coarse aggregate includes: 2 parts of impact crusher graded gravel with particle size of 0~2.36mm, 74 parts of impact crusher graded gravel with particle size of 2.36~4.75mm, 116 parts of impact crusher graded gravel with particle size of 4.75~9.5mm and 8 parts of impact crusher graded gravel with particle size of 9.5~19mm.

3. The alkali-activated pavement concrete using mountain tunnel slag according to claim 2, characterized in that: Both coarse aggregate and fine aggregate are obtained by crushing and shaping tunnel slag. The apparent density of coarse aggregate is 2.618t / m³, the volume density is 1.580t / m³, the water absorption rate is 2.4%, and the crushing value is 14.4%; the apparent density of fine aggregate is 2.7t / m³, the bulk density is 1.511t / m³, the mud content does not exceed 0.2%, the water content is 1.99%, and the fineness modulus is 2.

97.

4. The alkali-activated pavement concrete using mountain tunnel slag according to claim 1, characterized in that: Alkali-activated pavement concrete at a concentration of 10 mol / L NaOH solution includes the following raw materials in parts by mass: 108 parts of water, 32 parts of NaOH solid, 80 parts of fly ash, 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; among which, the 108 parts of water include 60 parts of mixing water and 48 parts of dissolved water.

5. The alkali-activated pavement concrete using mountain tunnel slag according to claim 1, characterized in that: Alkali-activated pavement concrete at a concentration of 12 mol / L NaOH solution includes the following raw materials in parts by mass: 101.6 parts of water, 38.4 parts of NaOH solid, 80 parts of fly ash, 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; among which, 101.6 parts of water include 60 parts of mixing water and 41.6 parts of dissolved water.

6. The alkali-activated pavement concrete using mountain tunnel slag according to claim 1, characterized in that: When the slag replacement rate is 20%, the alkali-activated pavement concrete at a concentration of 10 mol / L NaOH solution includes the following raw materials by weight: 108 parts of water, 32 parts of NaOH solid, 160 parts of fly ash, 40 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; Among them, 108 parts of water include 60 parts of mixing water and 48 parts of dissolving water; The fly ash was grade II with a particle size of 83 mm, and the slag powder was grade S95 with a particle size of 16 mm; 450 parts of fine aggregate include 9 parts of machine-made sand with a particle size of 0-0.15 mm, 35 parts of machine-made sand with a particle size of 0.15-0.3 mm, 158 parts of machine-made sand with a particle size of 0.3-0.6 mm, 158 parts of machine-made sand with a particle size of 0.6-1.18 mm, 45 parts of machine-made sand with a particle size of 1.18-2.36 mm, and 45 parts of machine-made sand with a particle size of 2.36-4.75 mm; The coarse aggregate includes 2 parts of impact crushed graded stone with a particle size of 0-2.36mm, 74 parts of impact crushed graded stone with a particle size of 2.36-4.75mm, 116 parts of impact crushed graded stone with a particle size of 4.75-9.5mm, and 8 parts of impact crushed graded stone with a particle size of 9.5-19mm; The apparent density of coarse aggregate is 2.62t / m³, the volume density is 1.581t / m³, the water absorption is 2.4%, and the crushing value is 14.4%; the apparent density of fine aggregate is 2.41t / m³, the bulk density is 1.514t / m³, the mud content does not exceed 0.2%, the water content is 1.99%, and the fineness modulus is 2.

97.

7. The alkali-activated pavement concrete using mountain tunnel slag according to claim 1, characterized in that: When the slag replacement rate is 40%, the alkali-activated pavement concrete at a concentration of 10 mol / L NaOH solution includes the following raw materials in parts by mass: 108 parts of water, 32 parts of NaOH solid, 120 parts of fly ash, 80 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer; 108 parts of water includes 60 parts of mixing water and 48 parts of dissolved water.

8. The alkali-activated pavement concrete using mountain tunnel slag according to claim 1, characterized in that: When the slag replacement rate is 60%, the alkali-activated pavement concrete at a concentration of 10 mol / L NaOH solution includes the following raw materials in parts by mass: 108 parts of water, 32 parts of NaOH solid, 80 parts of fly ash, 120 parts of slag powder, 200 parts of coarse aggregate, 450 parts of fine aggregate and 10 parts of polycarboxylate water reducer. The 108 parts of water include 60 parts of mixing water and 48 parts of dissolved water.

9. A method for preparing alkali-activated pavement concrete using mountain tunnel slag according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: preparing an alkali-activated mineral admixture mixture, mixing fly ash and slag powder according to mass percentage, dry-mixing and uniformly pouring into a stirring pot, and stirring at a constant speed for 30 seconds to obtain a first mixture; S2: adding mixing water and polycarboxylate water reducer, adding the mixing water and polycarboxylate water reducer into the first mixed material according to the mass percentage, stirring at a constant speed for 1 minute until the mixture is uniform, and obtaining a second mixed material; S3: preparing a NaOH solution, mixing dissolved water and NaOH solid particles according to mass percentage, stirring at a constant speed for 1 minute until the mixture is uniformly stirred, and obtaining a third mixture; S4: pouring the prepared third mixed material into the second mixed material, stirring at a constant speed for 30 seconds until the mixture is uniform, to obtain a fourth mixed material; S5: Add the coarse aggregate and the fine aggregate into the fourth mixture according to the mass percentage, and stir at a constant speed for 2 to 3 minutes until the mixture is uniformly stirred to obtain an alkali-activated pavement concrete material; S6: Cast the test specimen, add the alkali-activated pavement concrete material into a 150×150×150mm³ mold, vibrate it with a vibrator for 1 minute until no bubbles emerge on the surface, and smooth the surface; S7: Curing, cover the mold with a film and seal it to keep it moist and maintain it, then remove the mold and place it in a standard curing room for sealing and curing for 28 days; S8: Loading test: the mechanical properties of the cured specimens are tested in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB-T 50081-2019.

10. A method for preparing alkali-activated pavement concrete using mountain tunnel slag according to any one of claims 6 to 8, characterized in that: The following steps are involved: S1: Prepare an alkali-activated mineral admixture mixture, mix the fly ash and slag powder according to the mass percentage, dry mix and pour into a stirring pot, stir at a constant speed for 30s to obtain a first mixture; S2: adding mixing water and polycarboxylate water reducer, adding the mixing water and polycarboxylate water reducer into the first mixture according to the mass percentage, stirring at a constant speed for 1 minute until the mixture is uniform, and obtaining the second mixture; S3: preparing a NaOH solution, mixing dissolved water and NaOH solid particles according to mass percentage, stirring at a constant speed for 1 minute until the mixture is uniformly stirred, and obtaining a third mixture; S4: pouring the prepared third mixed material into the second mixed material, stirring at a constant speed for 30 seconds until the mixture is uniform, to obtain a fourth mixed material; S5: Add the coarse aggregate and the fine aggregate into the fourth mixture according to the mass percentage, and stir at a constant speed for 2 to 3 minutes until the mixture is uniformly stirred to obtain an alkali-activated pavement concrete material; S6: Cast the test specimen, add the alkali-activated pavement concrete material into a 150×150×150mm³ mold, vibrate it with a vibrator for 1 minute until no bubbles emerge on the surface, and smooth the surface; S7: Curing, the film covers the mold and moisturizes the seal and curing, then removes the mold and places it in a standard curing room for sealing and curing for 28d; S8: Loading test: the mechanical properties of the cured specimens are tested in accordance with the "Standard for Test Methods for Physical and Mechanical Properties of Concrete" GB-T 50081-2019.